How can quality of health care be safeguarded across the European Union? - Legido-Quigley, Helena; McKee, Martin; Walshe, Kieran; Suñol, Rosa; Nolte, Ellen; Klazinga, Niek (BMJ, 2008)
Can Europeans be confident about the quality of care received in another EU country? Helena Legido-Quigley and colleagues discuss the various mechanisms at work across Europe to ensure quality and safety